نمذجة موارد المياه الجوفية المضغوطة في المنطقة السهلية لحوض نهر بانياس - بدرحايك, شريف; عمار, غطفان; غانم, نور (Latakia University Journal -Engineering Sciences Series, 2019)
Based on necessity to find the best ways to invest and manage the available groundwater resources. We evaluated the confined water resources in the plain region of Banyas river catchment quantitatively, to predict the possible changes. The research area is located in the plain western part of the Banyas river catchment, and the area reach to 13 km². The research aims to create a numerical model of ground water movement, after development the conceptual model and calibrate it, prelude to put future investment scenarios, by the GMS-Modflow program, based on the measured monthly data between (2003-2004). We have created the optimal scenario to manage the available groundwater resources, by proposing drilling 30 wells, by discharging 2000-10000 m³/day per well. The results were concluded an increase in investment of wells to 278010 m³ per day, accompanied decreases in groundwater levels in the area wells ranged between (2-1) m. Which does not pose a threat to the investment of the aquifer. انطلاقاً من ضرورة إيجاد الطرائق المثلى لاستثمار وإدارة موارد المياه الجوفية المضغوطة المتاحة. قمنا بتقويم موارد المياه الجوفية المضغوطة في المنطقة السهلية لحوض نهر بانياس كمياً، والتنبؤ بالتغيرات المحتملة عليها. تقع منطقة البحث في الجزء الغربي السهلي من حوض نهر بانياس وتبلغ مساحة المنطقة حواليkm²13. يهدف البحث إلى بناء نموذج رياضـي لحركة المياه الجوفية فـي المنطقـة، بعـد تطوير النموذج الاعتباري ومعايرته، تمهيداً لوضع سيناريوهات الاستثمار المستقبليـة، وذلك باستخدام برنامج GMS-Modflow، بالاعتماد على البيانات الشهرية المقيسة ما بين عامي (2003-2004). قمنا بوضع السيناريو الأمثل لإدارة الموارد المائية الجوفية المتاحة، من خلال اقتراح حفر 30 بئراً، بتصريف m³/day 2000-10000 لكل بئر. وخلصت النتائج إلى ازدياد الاستثمارات من الآبار إلى m³278010 يومياً، وترافقت بهبوطات في مناسيب المياه الجوفية في آبار المنطقة تراوحت بين m (2-1). الأمر الذي لا يشكّل خطراً على استثمار طبقة المياه الجوفية.